Achieving E-Satisfaction in E-Commerce: The Relationship of TAM Factor on Repurchase Intention - Natasya Sharla Kirana; Timotius FCW Sutrisno; Anak Agung Ayu Puty Andrina (SAFE-Network, 2026)
This study aims to comprehensively examine the influence of factors in the Technology Acceptance Model (TAM) framework, namely ease of use, security, and privacy concerns on e-satisfaction, as well as the mediating role of e-satisfaction on the repurchase intention of Shopee users. The method used is quantitative research with a survey approach to 414 Ciputra University Surabaya students who have actively used the Shopee platform in the past month. Data analysis was performed using Partial Least Square Structural Equation Modeling (PLS-SEM). The results showed that ease of use and privacy concern had a significant effect on e-satisfaction, while security had no significant effect on either e-satisfaction or repurchase intention. Meanwhile, e-satisfaction proved to be the main predictor of repurchase intention, as well as an effective mediator in the relationship between ease of use and repurchase intention. These findings indicate a shift in e-commerce consumer preferences that no longer consider security as a value-add, but rather as a basic need that is already expected to be available. Instead, ease of use and privacy transparency are the main determinants in creating customer satisfaction and loyalty. Therefore, for e-commerce players like Shopee, customer retention strategies should focus on optimizing an intuitive user experience as well as a clear and easily accessible privacy policy. This research also extends the TAM framework by showing that privacy factors, while not directly influencing repurchase intentions, have an important role in creating e-satisfaction that impacts the long-term loyalty of digital customers.